Meta Analisis Kesulitan Belajar Materi Pecahan Matematika Siswa Kelas 3 SD - Putri Mas Intan Silalahi; Shofyani salasa; Demmina Ginting; Indah Mutia; Wildansyah Lubis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine students' difficulties in learning mathematics and the factors that contribute to their difficulties. This study used a qualitative approach with a descriptive qualitative research method intended to describe students' difficulties in learning mathematics. The subjects were ten third-grade students at an elementary school in Medan City. The results indicate that the difficulties experienced by students tend to be conceptual difficulties, where students do not fully understand the concept of fractions, have difficulty determining the numerator and denominator, write fractions in reverse, and have difficulty distinguishing between the symbols greater than (>) and less than (<). Factors contributing to students' difficulties in learning mathematics include low student attitudes and interest, a dislike of mathematics, which leads to students not paying attention to the teacher during mathematics lessons, resulting in a lack of enthusiasm for mathematics.